POSTGRADUATE STUDENTS’ PERCEPTIONS ON MOODLE AS LEARNING MANAGEMENT SYSTEM FOR ONLINE ENGLISH LANGUAGE LEARNING DURING COVID-19 PANDEMIC - Muhammad Shofiyuddin; Mutmainnah Mustofa; Mohammad Rizal Umam; Sonny Elfiyanto (Universitas Indraprasta PGRI, 2022)
In Indonesia, teaching learning process through Moodle as learning management system (LMS) has been implemented in education levels such as junior high schools, senior high school and universities. To find out the role of Moodle in learning English at a higher level, it is important to know whether students have different or the same perceptions about the use of Moodle in higher education, postgraduate level. The subject this research was postgraduate students from 3 different classes of English education department at University of Islam Malang. In this study, a qualitative method was used in the descriptive design, with an online questionnaire serving as the research instrument. Questionnaires are used to collect research data. There were 22 items in the questionnaires administered using Google Form that was purposed to know postgraduate students’ perceptions on Moodle at University of Islam Malang with 3 aspects to analyze; Moodle implementation, Moodle practicality, and online learning environment. The results revealed that studying English through Moodle was preferred with 66,7% of respondents agreed with the statement. For Moodle practicality, it was easy to run with 20 respondents agreed the statement or 60,6% as percentage. Online learning environment made students easier to comprehend lecturers’ explanation of materials given as 63,6% respondents agreed with the statement in the questionnaire. From those results, it could be concluded that Moodle was a preferred LMS. It was considered easy to use. Online learning environment also eased students to understand lecturers’ materials in English education department